Untargeted lipidomics reveals unique lipid signatures of extracellular vesicles from porcine colostrum and milk - Rafaela Furioso Ferreira; Morteza H. Ghaffari; Fabrizio Ceciliani; Manuela Fontana; Donatella Caruso; Matteo Audano; Giovanni Savoini; Alessandro Agazzi; Vladimir Mrljak; Helga Sauerwein (PLoS ONE, 2025)
Extracellular vesicles (EV) are membranous vesicles considered as significant players in cell-to-cell communication. Milk provides adequate nutrition, transfers immunity, and promotes neonatal development, and milk EV are suggested to play a crucial role in these processes. Milk samples were obtained on days 0, 7, and 14 after parturition from sows receiving either a standard diet (ω-6:ω-3 = 13:1) or a test diet enriched in ω-3 (ω-6:ω-3 = 4:1). EV were isolated using ultracentrifugation coupled with size exclusion chromatography, and characterized by nanoparticle tracking analysis, transmission electron microscopy, and assessment of EV markers via Western blotting. The lipidome was determined following a liquid chromatography–quadrupole time-of-flight mass spectrometry approach. Here, we show that different stages of lactation (colostrum vs mature milk) have a distinct extracellular vesicle lipidomic profile. The distinct lipid content can be further explored to understand and regulate milk EV functionalities and primordial for enabling their diagnostic and therapeutic potential.